The stylistic change in Kandinsky and Mondrian paintings (Al-Academy, 2018)
The current rasearch which is entitled " The stylistic change in Kandinsky and Mondrian paintings – A Comparative Analytic study-" deals with the nature of change concept, its mechanisms and its constructive disciplines. The research has four chapters: The first chapter deals with the methodological Framework represented by the problem of the research which is concerned with the stylistic change and its role in activating formative disciplines. The research aims at, finding out the stylistic change in Kandinsky and Mondrian Paintings. The limits of the research is restricted by analyzing pictorial models for both of painters between ( 1906- 1943). The second chapter which is represented by Theoretical Framework, has involved Three sections: The first section deals with the meaning of style, While the second section deals with the Abstract Expressionism trend and its Philosophy . The third section concerns with the study of Geometrical Abstract. The Third chapter deals with the research's procedures . It includes The research PoPulation and its sample which has(4) models. It also contains the tool of the research and the sample's analysis. The Fourth chapter includes the research's conclusion. The researcher has drawn several conclusion as an answer to the aim of the current research as:- 1-The repetition which gives a feeling of existence which is expressed by time movement, has an intertextuality with coloured and formative abstinence that effected on roles' exchange and the osmosis of sectors in location and time, towards the noblest aim represented by "Potential Beauty" not only in subjects, but also in essence as in figures (2, 4). 2- Calligraphy is considered as a type of music in Kandinsky& Mondrian Painting s . It is a semiotic Language out of visual language that can be understood in a comprehensive conceptual shape. in figures (2, 4).